The Impact of Technostress, Self-Efficacy, and Work-Life Balance on Employee Performance at LLDIKTI Region II - Diana, Putri Uki; Hildayanti, Siti Komariah; Handayani, Susi (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to analyze the influence of technostress, self-efficacy, and work-life balance on employee performance at LLDIKTI Region II. A quantitative approach was used with a saturated sampling technique. Data were collected through questionnaires completed by 60 respondents and analyzed using multiple linear regression with IBM SPSS version 27. The results show that technostress, self-efficacy, and work-life balance all have a positive and significant effect on employee performance, both partially and simultaneously. Among these, work-life balance has the greatest influence, followed by self-efficacy and technostress. The coefficient of determination (R²) of 53.1% indicates that these three variables explain more than half of the variation in employee performance. These findings imply that in facing digital transformation, LLDIKTI Region II needs to pay special attention to the factors affecting employee performance, particularly in managing technostress and enhancing self-efficacy. Practical recommendations for LLDIKTI Region II include providing regular technology training, implementing mentorship programs for senior employees, and offering self-efficacy enhancement programs through coaching and mentoring. Additionally, adopting flexible work policies is crucial to support employees’ work-life balance, ensuring optimal productivity in a dynamic digital work environment.